Effects of mycophenolate mofetil, methotrexate and pimecrolimus on cdk4 and p16 in erosive oral lichen planus - Sinny Goel; Nita Khurana (Wolters Kluwer Medknow Publications, 2021)
Background: This study evaluated the effect of mycophenolate mofetil, methotrexate, and pimecrolimus on the expression of cdk4 and p16, important proteins implicated in hyperproliferation and arrest in the G1 phase, in oral lichen planus (OLP). Materials and Methods: In this randomized clinical trial, 60 patients were randomly assigned in three equal groups to receive either pimecrolimus cream, or mycophenolate mofetil or methotrexate, both supplemented with pimecrolimus. Pretreatment and post-treatment specimens were immunohistochemically stained for detecting cdk4 and p16. Results: A significant decrease in cdk4 cytoplasmic positivity was noted in all three treatment groups and was especially more significant in the MTX group (P < 0.0001) than in the other two groups (P < .001). However, a significant decrease in the cdk4 nuclear staining was noted with only systemic treatment groups of MMF (P < 0.05) and MTX (P < 0.01), both supplemented with pimecrolimus. No significant decrease in cytoplasmic p16 levels was noted in the MTX group while a significant decrease in cytoplasmic p16 levels was noted in the other two groups; however, no significant decrease in p16 nuclear staining was noted with any treatment. Conclusion: By decreasing the expression of cdk4 and p16, pimecrolimus, methotrexate, and mycophenolate mofetil decrease the malignant potential of OLP lesions. However, methorexate can be a better alternative in cases showing high cdk4 expression.